Hvorfor spilde tiden med kvindelig idrætsledelse? - Ytting, Linnea (Forum for Idræt, 2006)
Artiklen med undertitlen ’Kønskonstruktioner og ligestillingsmæssige tiltag i den frivillige idrætsledelse’ har til formål at vise de kønskonstruktioner, der eksisterer i idrætsorganisationerne, og som har indflydelse på forudsætningerne for kvinders besiddelse af lederposter i organisationerne. Linnea Ytting: Why waste time on female sport leadership? About gender construction, gender equality in the voluntary sport organizations The sports organisations Danmarks Idræts- Forbund (DIF) and Danske Gymnastik- og Idrætsforeninger (DGI) have few women represented in their top leader positions. Both organisations have approximately 50% female membership and represent the entire Danish organised sport field. This is a sad fact, because women and men in many areas have different interests in sports. This article analyses some of the gender constructions of 6 young men and women in voluntary leadership, within chosen sports organisations. The purpose is to find the meaning of gender and describe how it is interpreted by the women and men in leading positions. The result of this research shows that many women are not interested in leading positions higher than club level. At the same time however, the structure of organisations are limiting, as to women wanting to achieve a higher voluntary leading position. Therefore it can be established that women must want the power, but the power must also want the women. In 2002 the political mainstreaming project was offered to sports organisations, introducing the gender problem on the political agenda. The political dimensions will therefore be included in the article, because the consequences may affect the sports organisations